The relationship between family support factors and substance abuse relapse: an updated literature review - Astyningtyas, Laila (ACTA Medical Health Sciences, 2025)
Current global data indicate that 296 million individuals engage in drug abuse, representing an increase of 12 million compared to previous figures. In Indonesia, the prevalence was 1.73%, with 173 individuals having used drugs in the past year. This study aimed to examine the supportive factors and challenges faced by substance abusers in overcoming dependence, achieving abstinence, and preventing relapse, focusing on resilience, self-esteem, and family functioning. This study employed a literature review methodology. Literature sources were identified using search engines through electronic media, including Google Scholar, PubMed, and ScienceDirect, covering publications from 2014 to 2024. The selected articles were assessed and evaluated based on predefined inclusion criteria, resulting in a final selection of 20 articles relevant to the topic. The findings indicate that the risk of relapse can be minimized with strong social support, especially from family members, which increases self-efficacy and resilience, thereby strengthening commitment to treatment. Therefore, intervention strategies that focus on improving family dynamics, strengthening self-esteem, and enhancing resilience are essential to facilitate sustainable recovery for individuals with substance use disorders. Family support has a positive impact on reducing the likelihood of relapsing in substance abusers. This article also compared similar findings from previous studies and presented the latest expert opinions supporting the importance of family communication in drug prevention. Adequate family support, in the form of communication and emotional support, can increase the resilience of substance users, thereby minimizing the risk of relapse in substance abuse. DOI : 10.35990/amhs.v3n3.p163-177 REFERENCES National Survey on Drug Abuse. 2023. Fatseas M, Kervran C, Auriacombe M. Troubles du sommeil et addictions: Impact sur la qualité de vie et le risque de rechute. Presse Medicale. 2016;45:1164–9. Lopes-Rosa R, Kessler FP, Pianca TG, Guimarães L, Ferronato P, Pagnussat E, et al. Predictors of early relapse among adolescent crack users. J Addict Dis. 2017;36(2):136–43. Andersson HW, Wenaas M, Nordfjærn T. Relapse after inpatient substance use treatment: A prospective cohort study among users of illicit substances. Addict Behav. 2019;90:222–8. Kabisa E, Biracyaza E, Habagusenga J d’Amour, Umubyeyi A. Determinants and prevalence of relapse among patients with substance use disorders: Case of Icyizere Psychotherapeutic Centre. Subst Abuse Treat Prev Policy. 2021;16(1). Perwita Sari A, Umbul Wahyuni C, Wibowo A. Social support and substance abuse relapse. Health Notions. 2018;2(1). Available from: http://heanoti.com/index.php/hn/article/view/hn20112 Nikmanesh Z, Baluchi MH, Motlagh AAP. The role of self-efficacy beliefs and social support on prediction of addiction relapse. Int J High Risk Behav Addict. 2017;6(1). Stevens E, Jason LA, Ram D, Light J. Investigating social support and network relationships in substance use disorder recovery. Subst Abus. 2015;36(4):396–9. Atadokht A, Hajloo N, Karimi M, Narimani M. The role of family expressed emotion and perceived social support in predicting addiction relapse. Int J High Risk Behav Addict. 2015;4(1). Torrecillas FL. Predictive capacity of self-efficacy in drug dependence and substance abuse treatment. J Psychol Clin Psychiatry. 2015;2(3). American Addiction Center. Addiction relapse: Risk factors, coping & treatment options. 2024. Wang YJ, Tang SS, Chen GD, Xia JH, Wang LN, Zhang H Le. Effect of family intervention on relapse rate of Chinese patients with alcohol dependence. Front Public Health. 2024;12. Venkateswaran S, Thirumalai R. A follow-up study on coping strategies and its association with relapse among alcohol-dependent patients. Indian J Psychol Med. 2024;46(3):245–52. Jan F, Iqbal N, Wasif S, Hassan B, Mushtaq R. Family functioning and relapse among drug addicts: Mediating role of psychological capital. Pak J Psychol Res. 2023;38(4):579–91. Mardani M, Alipour F, Rafiey H, Fallahi-Khoshknab M, Arshi M. Challenges in addiction-affected families: A systematic review of qualitative studies. BMC Psychiatry. 2023;23(1). Mohd Ghazalli FS, Ramly AF. Readiness of families to support a community-based drug rehabilitation program: A case study in Terengganu. Int J Acad Res Bus Soc Sci. 2023;13(12). Liu L, Meng W, Liu B. The mediating role of social support in the relationship between parenting styles and adolescent drug abuse identification. Front Psychol. 2022;12. Singh R, Goyal E, Chaudhury S, Puria A, Kumar S, Kumar A. Psychiatric morbidity in family members of alcohol dependence patients. Ind Psychiatry J. 2022;31(2):306–12. Hong P, Li S, Yu Y, Deng Q. How to enhance the motivation for drug detoxification: Consciousness guidance and behaviour restriction of family intergenerational ethics. Int J Environ Res Public Health. 2022;19(1). Rathinam B, Ezhumalai S. Resilience among abstinent individuals with substance use disorder. Zeng X, Lu M, Chen M. The relationship between family intimacy and relapse tendency among people who use drugs: A moderated mediation model. Subst Abuse Treat Prev Policy. 2021;16(1). Nawi AM, Ismail R, Ibrahim F, Hassan MR, Manaf MRA, Amit N, et al. Risk and protective factors of drug abuse among adolescents: A systematic review. BMC Public Health. 2021;21(1). Lee SB, Chung S, Seo JS, Jung WM, Park IH. Socioeconomic resources and quality of life in alcohol use disorder patients: The mediating effects of social support and depression. Subst Abuse Treat Prev Policy. 2020;15(1). Sarmawati, Ghozali MH. Literature review: Hubungan antara dukungan keluarga dengan kepatuhan pengguna narkoba menjalani therapeutic community. Vol. 2. Kang SK, Kim HJ, Shin S. A qualitative case study on recovery and personal growth in Korean drug addicts. J Soc Serv Res. 2018;44(3):279–90. Park GH, Choi YJ. Family stress and coping from hospitalization of clients with severe alcohol use disorder in Korea. J Addict Nurs. 2017;28(1):4–10. Asmoro DS, Melaniani S. Pengaruh lingkungan keluarga terhadap penyalahgunaan NAPZA pada remaja. Kesehatan Masyarakat Universitas Airlangga. Nasution J, Marliyah Z. The impact of drug abuse on social and family economics in the perspective of Sharia economics (Case Study at Baitu Syifa Drug Rehabilitation Institution in Medan). EKOMBIS Review. 2024;12(1):12. Available from: https://jurnal.unived.ac.id/index.php/er Xia Y, Gong Y, Wang H, Li S, Mao F. Family function impacts relapse tendency in substance use disorder: Mediated through self-esteem and resilience. Front Psychiatry. 2022;13. Zeng X, Tan C. The relationship between family functioning of individuals with drug addiction and relapse tendency: A moderated mediation model. Int J Environ Res Public Health. 2021;18(2):1–12. Afaf SN. Factors associated with relapse for patients with substance use disorder: An integrative review. NeuroQuantology. 2022;20(7):2974–82. Available from: www.neuroquantology.com Senormanci G, Esmen E, Turan C, Senormanci O. Evaluation of resilience, quality of life, and depression in family members of alcohol or substance dependent patients. Dusunen Adam. 2019;32(4):320–7. Tarantino N, Lamis DA, Ballard ED, Masuda A, Dvorak RD. Parent-child conflict and drug use in college women: A moderated mediation model of self-control and mindfulness. J Couns Psychol. 2015;62(2):303–13. Xie Q, Bi T, Du Y, Kou H, Yang B. Childhood maltreatment is associated with aggression among male juvenile delinquents in China: The mediating effects of callous-unemotional traits and self-control. Front Psychol. 2020;11. Tomori C, Go VF, Tuan LN, Huong NM, Binh NT, Zelaya CE, et al. “In their perception we are addicts”: Social vulnerabilities and sources of support for men released from drug treatment centers in Vietnam. Int J Drug Policy. 2014;25(5):897–904. Ramsewak S, Putteeraj M, Somanah J. Exploring substance use disorders and relapse in Mauritian male addicts. Heliyon. 2020;6(8). Taplin C, Saddichha S, Li K, Krausz MR. Family history of alcohol and drug abuse, childhood trauma, and age of first drug injection. Subst Use Misuse. 2014;49(10):1311–6. Rogers CJ, Forster M, Sussman S, Steinberg J, Barrington-Trimis JL, Grigsby TJ, et al. The impact of childhood trauma on problematic alcohol and drug use trajectories and the moderating role of social support. Int J Environ Res Public Health. 2023;20(4). Incerti L, Henderson-Wilson C, Dunn M. Challenges in the family: Problematic substance use and sibling relationships. Int J Qual Stud Health Well-being. 2014. Lindeman SK, Selseng LB, Lorås L, Løberg AH. Living with sibling's drug use: Bereaved siblings’ family stories. Int J Qual Stud Health Well-being. 2023;18(1). Studi P, Komunikasi I, Dakwah F, Komunikasi D, Ampel S, Yani Sja, et al. Komunikasi interpersonal rehabilitasi pecandu narkoba di Malang. J Ilmu Komunikasi. 2020;10(1). Available from: http://jurnalfdk.uinsby.ac.id/index.php/jik Massey SH, Newmark RL, Wakschlag LS. Explicating the role of empathic processes in substance use disorders: A conceptual framework and research agenda. Drug Alcohol Rev. 2018;37:316–32. Shehata MH, Ebrahim SN. Effectiveness of strengthening resilience training program on patients with substance abuse. IOSR J Nurs Health Sci. 8(3):63–72. Calpe-López C, Martínez-Caballero MA, García-Pardo MP, Aguilar MA. Resilience to the effects of social stress on vulnerability to developing drug addiction. World J Psychiatry. 2022;12(1):24–58. Blain-Arcaro C, Vaillancourt T. Longitudinal associations between depression and aggression in children and adolescents. J Abnorm Child Psychol. 2017;45(5):959–70. Dallas JC, Jullamate P, Vatanasin D, Moungkum S, Nadarajan S, Krungkraipetch N. Resilience and influencing factors among youths undergoing substance abuse treatment in Thailand: A cross-sectional study. SAGE Open Nurs. 2023;9.